THE EFFECT OF LABOR AND FINANCIAL FRICTIONS ON AGGREGATE FLUCTUATIONS. (29th December 2014) - Mumtaz, Haroon; Zanetti, Francesco
Abstract : This paper embeds labor market search frictions into a New Keynesian model with financial frictions. The econometric estimation establishes that labor market frictions substantially improve the empirical fit of the model. The effect of the interaction between labor and financial frictions on aggregate fluctuations depends on the nature of the shock. For monetary policy, technology, and entrepreneurial wealth shocks, labor market frictions amplify the effect of financial frictions, because robust changes in hiring lead to persistent movements in employment and return on capital that reinforce the original effect of financial frictions. For cost-push, labor supply, marginal efficiency of investment, and preference shocks, labor market frictions dampen the effect of financial frictions by reducing the real cost of repaying existing debt, which lowers the external finance premium.